Analisis tata ruang layanan referensi di Perpustakaan Daerah Kota Payakumbuh - Cut Afrina; Shalsa Nabhila; Yayang Putri (Al-Kuttab : Jurnal Kajian Perpustakaan, Informasi dan Kearsipan, 2022)
This study discuss how the spatial layout of the reference service owned by the Regional Library of Payakumbuh ca be used as an analysis of the spatial layout of reference service from other regional libraries. For the analysis of the spatial layout itself, it can be seen from how the placement of the room by the Payakumbuh local library is to increase the quality of the reference services they already have. In this study, researchers used qualitative research methods by conducting field observations. From the result of the study, it can be shown that the layout of the reference services in the Regional Library of Payakumbuh City can be said to be inadequate because the layout is still joined with other services such as children’s services, nursing mothers’ rooms, and IT rooms. Therefore, the users who come to this reference service room feel uncomfortable because the size of the room is 5x6 meters. The lack of facilities in the Payakumbuh Regional library is because the building is still joined by other agencies, namely the tourism and sports office, and the food security service. Reportedly, in 2024, this library will become its building and will longer be affiliated with the government agency. It’s hoped that with this good news that will be carried out by the regional library of the city of payakumbuh, the layout of the reference service will become wider in size and will no longer be combined with other services. Therefore, the purpose of this reference service is to make it easier for users to search or search for information.